Investing in women livestock advisers and farmers: Jharkhand Opportunities for Harnessing Rural Growth Programme in India - Kumar, Anish; Kumar, Ashok; Kumar, Manish; Bhardwaj, Rajeev; Bhengra, Vishal; Davis, Kristin E.; Dutta, Pratham; Ekka, Nilima; Gilbert, Rachel; Kumar, Priti; Leitch, Helen; Ngwenya, Hlamalani; et al. (Food and Agricultural Organization of the United Nations, 2021)
Investing in farmers – or agriculture human capital – is crucial to addressing challenges in our agri-food systems. A global study carried out by the FAO Investment Centre and the International Food Research Institute, with support from the CGIAR Research Programme on Policies, Institutions and Markets and the FAO Research and Extension Unit, looks at agriculture human capital investments, from trends to promising initiatives. One of the nine featured case studies is the Jharkhand Opportunities for Harnessing Rural Growth Programme in India. This case explores investment in developing the human capital of women livestock farmers as certified master trainers and community service providers known as Ajeevika Pashu Sakhi (APS). The livestock farmers were strategically identified, trained and coached as APSs to provide doorstep technical, marketing and risk reduction support to women livestock farmers. The APSs were supported by certified master trainers. The APS model enhanced the economic and social well-being of rural poor women working as livestock farmers and APSs. This publication is part of the Country Investment Highlights series under the FAO Investment Centre's Knowledge for Investment (K4I) programme.